FACTORS RELATING TO COMPLIANCE OF NURSES IN IMPLEMENTING SOP BUNDLE HEALTHCARE ASSOCIATED INFECTIONS (HAIs) IN ADVENT HOSPITAL IN BANDUNG - Lerson Hutagaol; Yayat Suryani; Lilis Rohayani; Asep Setiawan; Murtiningsih Murtiningsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Background: The incidence of HAIs at the Bandung Adventist Hospital in 2019 is still quite high, where the incident rate of HAIs is 18% VAP, 13% UTI, 7% phlebitis, 1% HAP, and 4% SSI. Nurses' compliance in implementing the HAIs bundle is very important to do as a form of patient safety. Nurse compliance can be increased by applying the appropriate leadership style by the head of the room. This study aims to analyze the factors associated with nurse compliance in implementing the SOP bundle of HAIs in the inpatient room of the Bandung Advent Hospital. The research method: Analytical survey with correlation design. The research sample was 62 respondents who were taken by using proportional random sampling. The variables of age, sex, and years of service were measured using a checklist questionnaire. Leadership style is measured using a questionnaire with a Semantic Differential scale (1-8), and compliance is measured by observing nurses in implementing SOP bundles of HAIs, including SOP Bundles of ISK, IAD, VAP, IDO. Data were analyzed using univariate, bivariate (chi square), and multivariate (multiple logistic regression). Results: The results of the Chi Square test show that there is a relationship between tenure and compliance with the ISK bundle, and there is a relationship between leadership style and compliance with the implementation of the HAIs SOP bundle and the IDO bundle. The results of regression analysis showed that democratic and authoritarian leadership styles were the types of leadership styles that were most related to nurses' compliance in implementing the SOP bundle of HAIs (p 0.018), especially in the implementation of the IAD bundle SOP (p 0.040).